Diabetic Retinopathy, Superoxide Damage and Antioxidants - Santos, Julia M. (2011)
Retinopathy, the leading cause of acquired blindness in young adults, is one of the most feared complications of diabetes, and hyperglycemia is considered as the major trigger for its development. The microvasculature of the retina is constantly bombarded by high glucose, and this insult results in many metabolic, structural and functional changes. Retinal mitochondria become dysfunctional, its DNA is damaged and proteins encoded by its DNA are decreased. The electron transport chain system becomes compromised, further producing superoxide and providing no relief to the retina from a continuous cycle of damage. Although the retina attempts to initiate repair mechanisms by inducing gene expressions of the repair enzymes, their mitochondrial accumulation remains deficient. Understanding the molecular mechanism of mitochondrial damage should help identify therapies to treat/retard this sight threatening complication of diabetes. Our hope is that if the retinal mitochondria are maintained healthy with adjunct therapies, the development and progression of diabetic retinopathy can be inhibited.